Outcome of Corticosteroid Injection for Sciatica through the Caudal Route - KC, Nagendra Bahadur; Shrestha, Shriraj (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Sciatica is an important medical problem with socioeconomic impact; its effective management remains a challenge. Approximately 80% of the total population experiences low back pain at some point in their lives which may be associated with sciatica. As it is more common in adult working group, the pain caused by sciatica can incapacitate a person fromdoing his or her normal work. So the goal of our treatment is not to cure anatomic abnormalities but rather to reduce pain, which allows the patient to engage in early rehabilitation and return to a more normal lifestyle. Methods: Fifty patients were initially included in the study and all patients received three injection of 4ml methyle prednisolone acetate (160 mg) and 6 ml of Normal saline that is of total volume 10 ml.at an interval of 48 hours. Among 50 study patients, five patients dropped out in subsequent follow-up. So only forty-five patients were analyzed for final results. Results: The mean age of the patient was 37.53 years, majority between 30-56 years. Female who were involved in household activities dominated the study group. Comparing the mean (SD) VAS score on the day of presentation 70.00 (16.78) and on 35th day 17.89 (25.23) so it was found to be statistically significant (P<0.001). None of the patients in the study had motor weakness and none of them developed serious complications. But 12 (26.7%) patients developed transient headache after the procedure. Conclusions: As the goal of our treatment was symptomatic pain relief, most of the patient’s pain improved at 2 weeks after the steroid injection with no severe complication. This was short term study with encouraging results, but larger scale and longer period of follow ups required for better results.